Market Competition in Modern Franchise Retail Business with Traditional Retail Business in Saddu Al-Zari'ah Approach - Fauziah, Fauziah; Arif, Widyantono (Journal of Multiperspectives on Accounting Literature, 2023)
Purpose: This article focuses on examining analysis in Islamic law on the existence of Alfamart and Indomaret minimarkets in Makassar City Methodology/approach: This research is a type of qualitative descriptive research, namely a writing procedure that produces descriptive data Findings: Based on the results of the study, it can be concluded that the existence of Alfamart and Indomaret minimarkets in their trading activities is reviewed in Islamic law including monopoly. Practical implications: As well as in its trading activities, it does not pay attention to business competition and the principle of justice in Islamic law. To prevent the expansion of the two minimarkets, Saddu Al-Zari'ah approach is needed so as not to have a bad impact on its competitors, namely grocery stores and traditional markets. Originality/value: Originality of this research is the subject using a Islamic law for trading activites. Keywords: Islamic Law; Minimarket; Monopoly; Traditional Market.